Negative electrode for secondary battery, and non-aqueous electrolyte secondary battery
By using more than 50 mass% of silicon-containing material in the negative electrode mixture layer of the secondary battery, and controlling its porosity and volume specific capacity/porosity values, the problems of large volume changes and insufficient durability during the charging and discharge process of silicon-containing material negative electrodes are solved, and the battery cycle characteristics of high capacity and high durability are achieved.
Patent Information
- Application Number
- CN202380059276.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-26
- Filing Date
- 2023-07-12
- Publication Date
- 2025-03-25
AI Technical Summary
In the prior art, the negative electrode using silicon-containing material changes in volume during charging and discharging, and its durability is insufficient, making it difficult to take into account both high capacity and high durability.
A negative electrode for secondary batteries was designed, and the mixture layer contained more than 50 mass% of silicon-containing material, with a porosity of more than 25%, and the circulation characteristics were improved by dividing the volume specific capacity by the value of porosity (48.0 mAh/cc·% or less).
Through this technical means, the circulation characteristics of the nonaqueous electrolyte secondary battery are significantly improved, taking into account high capacity and high durability.
Smart Images

Figure CN119698699A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to a negative electrode for a secondary battery and a nonaqueous electrolyte secondary battery using the negative electrode. Background Art
[0002] Silicon-containing materials have attracted attention as high-capacity negative electrode active materials. Patent Document 1 discloses a silicon-containing material that can be used for a negative electrode for a secondary battery and contains porous carbon and silicon. The silicon-containing material has 15% by mass or more and 85% by mass or less of silicon, 0.05 cm 3 / g or more and 0.5cm 3 / g or less nitrogen cannot enter or leave the volume, and 1.5cm 3 / g or more and 2.2g / cm 3 The particle skeleton density is as follows. Patent Document 1 attempts to achieve a high-capacity, high-durability, high-output battery by optimizing the true density and pore state of a silicon-containing material.
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent Document 1: Japanese Patent Application No. 2018-534720 Summary of the invention
[0006] The use of a negative electrode containing silicon material is effective for increasing the capacity of the battery, but the volume change of the silicon material accompanying charge and discharge is large, and there are technical problems in durability (charge and discharge cycle characteristics). Therefore, in the prior art including Patent Document 1, a larger amount of graphite than the silicon material is usually used in combination as the negative electrode active material, which makes it difficult to achieve both high capacity and high durability.
[0007] The negative electrode for a secondary battery disclosed in the present invention includes a core and a mixture layer arranged on the core, the mixture layer contains a silicon-containing material as an active material, the proportion of the silicon-containing material in the active material is more than 50% by mass, and the porosity is more than 25%, and the value obtained by dividing the volume specific capacity by the porosity is less than 48.0 mAh / cc·%.
[0008] The nonaqueous electrolyte secondary battery according to the present disclosure includes the above-mentioned negative electrode for a secondary battery, a positive electrode, and a nonaqueous electrolyte, and charge and discharge are controlled within a voltage range of 2.0V to 4.2V.
[0009] According to the secondary battery negative electrode according to the present disclosure, the cycle characteristics can be improved in a high-capacity nonaqueous electrolyte secondary battery including a silicon-containing material. BRIEF DESCRIPTION OF THE DRAWINGS
[0010] Figure 1 It is a cross-sectional view of a nonaqueous electrolyte secondary battery as an example of an embodiment. DETAILED DESCRIPTION
[0011] The inventors of the present invention have conducted in-depth research to improve the cycle characteristics in a high-capacity non-aqueous electrolyte secondary battery containing a large amount of silicon-containing materials. As a result, it was found that the relationship between the volumetric capacity and porosity of the negative electrode mixture layer containing silicon-containing materials is very important for improving the cycle characteristics. It can be seen that the negative electrode in which the proportion of silicon-containing materials in the negative electrode active material is more than 50% by mass usually has a large capacity drop with charge and discharge, but by controlling the value obtained by dividing the volumetric capacity of the negative electrode mixture layer by the porosity (volume specific volume / porosity) to less than 48.0mAh / cc·%, the above-mentioned capacity drop can be highly suppressed. The porosity in the present disclosure refers to the proportion of pores between the negative electrode active material particles in the mixture layer, and the pores within the active material particles are not included in the porosity.
[0012] From the perspective of cycle characteristics, batteries using negative electrodes containing a large amount of silicon-containing materials are considered difficult to use as batteries for, for example, vehicle-mounted applications, power storage applications, etc., but if pores far exceeding the scope of the prior art are introduced into the negative electrode mixture layer and the volume ratio / porosity is controlled below 48.0 mAh / cc·%, high capacity and high durability can be highly balanced. That is, in a non-aqueous electrolyte secondary battery containing a large amount of silicon-containing materials so that the proportion of silicon-containing materials in the negative electrode active material is 50% by mass or more, the cycle characteristics are specifically improved with a volume ratio / porosity of 48.0 mAh / cc·%. When the volume ratio / porosity of the negative electrode mixture layer is below 48.0 mAh / cc·%, the movement path of the cations in the negative electrode can be fully ensured, and the inhomogeneity of the battery reaction can be suppressed. As a result, it can be considered that the cycle characteristics are significantly improved.
[0013] Hereinafter, an example of an embodiment of a nonaqueous electrolyte secondary battery according to the present disclosure will be described in detail with reference to the drawings. It should be noted that a configuration in which each component of a plurality of embodiments and modifications described below is selectively combined is included in the scope of the present disclosure.
[0014] Hereinafter, as a non-aqueous electrolyte secondary battery, a cylindrical battery in which a wound electrode body 14 is contained in an outer can 16 having a bottomed cylindrical shape is exemplified, but the outer body of the battery is not limited to a cylindrical outer can. The non-aqueous electrolyte secondary battery involved in the present disclosure may be, for example, a square battery with a square outer can, a coin-shaped battery with a coin-shaped outer can, or a bag-shaped battery with an outer body composed of a laminate sheet including a metal layer and a resin layer. In addition, the electrode body is not limited to a wound type, and may also be a stacked electrode body in which a plurality of positive electrodes and a plurality of negative electrodes are alternately stacked with a separator.
[0015] Figure 1 FIG. 1 is a cross-sectional view of a nonaqueous electrolyte secondary battery 10 as an example of an embodiment. Figure 1 As shown, the nonaqueous electrolyte secondary battery 10 includes a wound electrode body 14, a nonaqueous electrolyte, and an outer can 16 that contains the electrode body 14 and the nonaqueous electrolyte. The electrode body 14 includes a positive electrode 11, a negative electrode 12, and a separator 13, and has a winding structure in which the positive electrode 11 and the negative electrode 12 are wound in a spiral shape with the separator 13 interposed therebetween. The outer can 16 is a metal container in a bottomed cylindrical shape with an opening at one end in the axial direction, and the opening of the outer can 16 is blocked by a sealing body 17. In the following, for the sake of convenience of explanation, the sealing body 17 side of the battery is set as the upper side, and the bottom side of the outer can 16 is set as the lower side.
[0016] The non-aqueous electrolyte has lithium ion conductivity and may be a liquid electrolyte (electrolyte) or a solid electrolyte.
[0017] Liquid electrolyte (electrolyte) comprises non-aqueous solvent and electrolyte salt dissolved in non-aqueous solvent. Non-aqueous solvent can use ester, ether, nitrile, amide and mixed solvent of two or more thereof, etc. as example. As an example of non-aqueous solvent, ethylene carbonate (EC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), diethyl carbonate (DEC) and mixed solvent thereof, etc. can be listed. Non-aqueous solvent can contain halogen substitution (such as fluoroethylene carbonate, etc.) formed by replacing at least a part of hydrogen in these solvents with halogen atoms such as fluorine. Electrolyte salt uses lithium salts such as LiPF6, etc.
[0018] As a solid electrolyte, for example, a solid or gel-like polymer electrolyte, an inorganic solid electrolyte, etc. can be used. As an inorganic solid electrolyte, well-known materials in all-solid-state lithium-ion secondary batteries, etc. (such as oxide-based solid electrolytes, sulfide-based solid electrolytes, halogen-based solid electrolytes, etc.) can be used. The polymer electrolyte, for example, contains a lithium salt and a matrix polymer; or a non-aqueous solvent, a lithium salt, and a matrix polymer. As a matrix polymer, for example, a polymer material that absorbs a non-aqueous solvent and gels is used. As polymer materials, fluororesins, acrylic resins, polyether resins, etc. can be listed.
[0019] The positive electrode 11, the negative electrode 12, and the separator 13 constituting the electrode body 14 are all strip-shaped long bodies, which are alternately stacked in the radial direction of the electrode body 14 by being wound into a spiral shape. In order to prevent the precipitation of lithium, the negative electrode 12 is formed to be one circle larger than the positive electrode 11. That is, the negative electrode 12 is formed longer than the positive electrode 11 in the length direction and the width direction. The separator 13 is formed to be at least one circle larger than the positive electrode 11, for example, two sheets are arranged to sandwich the positive electrode 11. The electrode body 14 has a positive electrode lead 20 connected to the positive electrode 11 by welding or the like, and a negative electrode lead 21 connected to the negative electrode 12 by welding or the like.
[0020] Insulating plates 18 and 19 are disposed above and below the electrode body 14, respectively. Figure 1In the example shown, the positive electrode lead 20 extends to the sealing body 17 side through the through hole of the insulating plate 18, and the negative electrode lead 21 extends to the bottom side of the outer can 16 through the outer side of the insulating plate 19. The positive electrode lead 20 is connected to the lower surface of the internal terminal plate 23 of the sealing body 17 by welding or the like, and the lid 27, which is the top plate of the sealing body 17 electrically connected to the internal terminal plate 23, becomes the positive terminal. The negative electrode lead 21 is connected to the inner surface of the bottom of the outer can 16 by welding or the like, and the outer can 16 becomes the negative terminal.
[0021] A sealing gasket 28 is provided between the outer can 16 and the sealing body 17 to ensure the airtightness inside the battery. A groove portion 22 is formed on the outer can 16 so that a part of the side surface bulges inward and supports the sealing body 17. The groove portion 22 is preferably formed in an annular shape along the circumference of the outer can 16, and the sealing body 17 is supported by its upper surface. The sealing body 17 is fixed to the upper part of the outer can 16 through the groove portion 22 and the open end of the outer can 16 that is closely fitted to the sealing body 17.
[0022] The sealing body 17 has a structure in which an internal terminal plate 23, a lower valve body 24, an insulating component 25, an upper valve body 26 and a lid 27 are stacked in order from the electrode body 14 side. The components constituting the sealing body 17 have, for example, a disc shape or a ring shape, and the components except the insulating component 25 are electrically connected to each other. The lower valve body 24 and the upper valve body 26 are connected at their respective central portions, and an insulating component 25 is sandwiched between their respective peripheral portions. When the internal pressure of the battery rises due to abnormal heat, the lower valve body 24 deforms and breaks to push the upper valve body 26 to the lid 27 side, thereby cutting off the current path between the lower valve body 24 and the upper valve body 26. When the internal pressure rises further, the upper valve body 26 breaks, and the gas is discharged from the opening of the lid 27.
[0023] Hereinafter, the positive electrode 11 , the negative electrode 12 , and the separator 13 constituting the electrode body 14 , particularly the configuration of the negative electrode 12 will be described in detail.
[0024] [positive electrode]
[0025] The positive electrode 11 has a positive electrode core 30 and a positive electrode mixture layer 31 disposed on the positive electrode core 30. The positive electrode core 30 can be made of a foil of a metal such as aluminum that is stable within the potential range of the positive electrode 11, a thin film having the metal disposed on the surface, or the like. The positive electrode mixture layer 31 contains a positive electrode active material, a conductive agent, and a binder, and is preferably disposed on both sides of the positive electrode core 30 except for the portion connected to the positive electrode lead 20. The positive electrode 11 can be manufactured, for example, by applying a positive electrode mixture slurry containing a positive electrode active material, a conductive agent, and a binder to the surface of the positive electrode core 30, drying the coating, and then compressing the positive electrode mixture layer 31 to form the positive electrode mixture layer 31 on both sides of the positive electrode core 30.
[0026] As the conductive agent contained in the positive electrode mixture layer 31, carbon black such as acetylene black and Ketjen black; carbon materials such as graphite, carbon nanotubes (CNT), carbon nanofibers, and graphene can be listed. As the binder contained in the positive electrode mixture layer 31, fluorine-containing resins such as polytetrafluoroethylene (PTFE) and polyvinylidene fluoride (PVDF), polyacrylonitrile (PAN), polyimide, acrylic resin, polyolefin, etc. can be listed. In addition, these resins can be used in combination with carboxymethyl cellulose (CMC) or its salt, polyethylene oxide, etc. The content of the conductive agent and the binder is, for example, 0.1% by mass or more and 5% by mass or less relative to the mass of the negative electrode mixture layer 31.
[0027] The positive electrode mixture layer 31 contains a lithium-containing transition metal oxide as a positive electrode active material. The lithium-containing transition metal oxide has, for example, a layered rock salt structure. As an example of a layered rock salt structure of a lithium-containing transition metal oxide, a layered rock salt structure belonging to the space group R-3m, a layered rock salt structure belonging to the space group C2 / m, etc. can be listed. Among them, from the perspective of high capacity and stability of the crystal structure, a layered rock salt structure belonging to the space group R-3m is preferred. The layered rock salt structure of the lithium-containing transition metal oxide includes a transition metal layer, a Li layer, and an oxygen layer.
[0028] The lithium-containing transition metal oxide contains metal elements such as Co, Mn, Ni, and Al in addition to Li. The metal elements constituting the lithium-containing transition metal oxide are, for example, at least one selected from Mg, Al, Ca, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Ga, Ge, Y, Zr, Sn, Sb, W, Pb, and Bi. Among them, it is preferred to contain at least one selected from Co, Ni, and Mn. As an example of a preferred composite oxide, a composite oxide containing Ni, Co, and Mn; a composite oxide containing Ni, Co, and Al can be listed.
[0029] The lithium-containing transition metal oxide may contain 50 mol %, 70 mol % or 80 mol % or more of Ni relative to the total molar number of metal elements other than Li. By increasing the content of Ni, it is easy to achieve high capacity of the battery. The content of Ni relative to the total molar number of metal elements other than Li can be 85 mol % or more, or 90 mol % or more. The upper limit of the Ni content is, for example, 95 mol %.
[0030] As described above, an example of a preferred lithium-containing transition metal oxide is a composite oxide containing Ni, Co, and Al. Relative to the total molar number of metal elements other than Li, the content of Al is 4 mol% or more and 15 mol% or less, and the content of Co is 1.5 mol% or less. If the content of Al is within this range, the crystal structure is stabilized and contributes to the improvement of the cycle characteristics. Co may not be substantially added, but the battery performance can be improved by adding a small amount of Co.
[0031] Lithium-containing transition metal oxides are, for example, of the general formula Li a Ni x Al y Co z M w O 2-b The composite oxide shown in the formula, wherein 0.8≤a≤1.2, 0.50≤x≤0.95, 0≤y≤0.10, 0≤z≤0.015, 0≤w≤0.50, 0≤b<0.05, x+y+z+w=1, and M is at least one element selected from Mn, Fe, Ti, Si, Nb, Zr, Mo and Zn.
[0032] The content of the elements constituting the lithium-containing transition metal composite oxide can be measured by an inductively coupled plasma atomic emission spectrometer (ICP-AES), an electron beam microanalyzer (EPMA), an energy dispersive X-ray analyzer (EDX), or the like.
[0033] The lithium-containing transition metal composite oxide can be a secondary particle formed by the aggregation of multiple primary particles. The volume-based median particle size (D50) of the composite oxide is not particularly limited, for example, it is greater than 3 μm and less than 30 μm, preferably greater than 5 μm and less than 25 μm. When the composite oxide is a secondary particle aggregated by primary particles, the D50 of the composite oxide refers to the D50 of the secondary particle. D50 refers to the particle size when the cumulative frequency in the volume-based particle size distribution reaches 50% from the side with a smaller particle size, also known as the median diameter. The particle size distribution of the composite oxide (also the case for the negative electrode active material) can be measured using a laser diffraction particle size distribution measuring device (for example, MT3000II manufactured by Microtrac Bell) and water as the dispersion medium.
[0034] [negative electrode]
[0035] The negative electrode 12 includes a negative electrode core 40 and a negative electrode mixture layer 41 disposed on the negative electrode core 40. The negative electrode core 40 may be made of a foil of a metal such as copper that is stable within the potential range of the negative electrode 12, or a thin film having the metal disposed on the surface. The negative electrode mixture layer 41 includes a negative electrode active material and a binder, and is preferably disposed on both surfaces of the negative electrode core 40 except for the portion connected to the negative electrode lead 21. The negative electrode 12 may be manufactured, for example, by coating a negative electrode mixture slurry including a negative electrode active material and a binder on the surface of the negative electrode core 40, drying the coating, and then compressing the coating to form the negative electrode mixture layer 41 on both surfaces of the negative electrode core 40.
[0036] Similar to the case of the positive electrode 11, the binder contained in the negative electrode mixture layer 41 can also use fluororesin, PAN, polyimide, acrylic resin, polyolefin, etc., but preferably styrene-butadiene rubber (SBR) is used. In addition, the negative electrode mixture layer 41 preferably contains CMC or its salt, polyacrylic acid (PAA) or its salt, polyvinyl alcohol (PVA), etc. Among them, SBR is preferably used in combination with CMC or its salt, PAA or its salt. The content of the binder relative to the mass of the negative electrode mixture layer 41 is, for example, greater than 0.1% by mass and less than 5% by mass. It should be noted that the negative electrode mixture layer 41 may also contain a conductive agent such as CNT.
[0037] The negative electrode mixture layer 41 contains a silicon-containing material as a negative electrode active material. The proportion of the silicon-containing material in the negative electrode active material is 50% by mass or more. Compared with carbon-based active materials such as graphite commonly used as negative electrode active materials, silicon-containing materials can absorb more Li ions, so by increasing the content of silicon-containing materials, the battery capacity can be increased. As described later, simply increasing the content of silicon-containing materials will lead to a significant decrease in cycle characteristics. To this end, in order to achieve both high capacity and high durability in the non-aqueous electrolyte secondary battery 10, the porosity of the negative electrode mixture layer 41 is set to 25% or more, and the value obtained by dividing the volumetric capacity of the negative electrode mixture layer 41 by the porosity (hereinafter referred to as "volume specific capacity / porosity") is set to 48.0 mAh / cc·% or less.
[0038] The proportion (content) of the silicon-containing material in the negative electrode active material is preferably 60% by mass or more, more preferably 70% by mass or more, particularly preferably 80% by mass or more, and may be 90% by mass or more. The upper limit of the content of the silicon-containing material is not particularly limited and may be 100% by mass. An example of a preferred range of the content of the silicon-containing material is 70% by mass or more and 100% by mass or less of the mass of the negative electrode active material, more preferably 80% by mass or more and 100% by mass or less. The negative electrode mixture layer 41 may substantially contain only the silicon-containing material as the negative electrode active material, but may also contain a carbon material in an amount of 50% by mass or less.
[0039] The carbon material that functions as the negative electrode active material is, for example, at least one selected from the group consisting of natural graphite, artificial graphite, soft carbon and hard carbon. Among them, as the carbon material, it is preferred to use at least artificial graphite such as blocky artificial graphite (MAG), graphitized mesophase carbon microbeads (MCMB), natural graphite such as flaky graphite, blocky graphite, and earthy graphite, or a mixture thereof. The volume-based D50 of the carbon material is, for example, 1 μm or more and 30 μm or less, preferably 5 μm or more and 25 μm or less.
[0040] Soft carbon and hard carbon are classified as amorphous carbon with an underdeveloped graphite crystal structure. More specifically, it refers to a carbon component with a d(002) plane spacing of 0.342 nm or more based on X-ray diffraction. Soft carbon is also called easily graphitized carbon, which is carbon that is more easily graphitized by high-temperature treatment than hard carbon. Hard carbon is also called difficult to graphitize carbon. It should be noted that the composition of the present invention does not require a clear distinction between soft carbon and hard carbon. As a negative electrode active material, graphite can be used in combination with amorphous carbon of at least one of soft carbon and hard carbon.
[0041] As described above, the volumetric capacity / porosity of the negative electrode mixture layer 41 is 48.0 mAh / cc·% or less. It can be considered that the pores between the particles of the negative electrode active material become the main movement path of the Li ions that move in the negative electrode mixture layer 41 during charging and discharging. It can be considered that if the volumetric capacity / porosity value of the negative electrode mixture layer 41 is 48.0 mAh / cc·% or less, the movement path of the Li ions is fully ensured. In addition, it can be considered that if it is 48.0 mAh / cc·% or less, the effect of the expansion of the silicon-containing material during charging can be fully alleviated. If the volumetric capacity / porosity is 48.0 mAh / cc·% or less, for this reason, the capacity decrease accompanying charging and discharging is highly suppressed, and the cycle characteristics are significantly improved.
[0042] The cycle characteristics of the non-aqueous electrolyte secondary battery 10 vary significantly with the volumetric capacity / porosity of the negative electrode mixture layer 41 at 48.0 mAh / cc·%, so from the perspective of battery performance stability, the volumetric capacity / porosity is controlled to be below 45.0 mAh / cc·%. An example of a preferred volumetric capacity / porosity is below 45.0 mAh / cc·% or below 40.0 mAh / cc·%.
[0043] The lower limit of the volumetric capacity / porosity of the negative electrode mixture layer 41 is not particularly limited, but even if it is excessively reduced, the improvement effect of the cycle characteristics has reached a limit, so it is preferably 25.0 mAh / cc·%, and more preferably 30.0 mAh / cc·%. If the volumetric capacity / porosity of the negative electrode mixture layer 41 is 48.0 mAh / cc·% or less and 25.0 mAh / cc·% or more or 30.0 Ah / cc·% or more, it is possible to achieve both high capacity and high durability at a higher level.
[0044] In the present disclosure, the volumetric specific capacity of the negative electrode mixture layer is measured by the following method.
[0045] (1) The battery to be evaluated was disassembled and the negative electrode plate was cut out. Metal Li was used as the counter electrode and ionic liquid was used as the electrolyte to make a monopolar battery.
[0046] (2) The monopolar battery was charged at 0.1C in a temperature environment of 25°C until the battery voltage reached 5 mV, and after a 20-minute pause, it was discharged at 0.1C until the battery voltage reached 1.0 V. The discharge capacity (C) was calculated.
[0047] (3) The discharge capacity (C) was divided by the volume (Va) of the negative electrode mixture layer in the discharged state to calculate the volumetric capacity (Cv (mAh / cc) = C / Va).
[0048] The porosity of the negative electrode mixture layer 41 is greater than 25%, preferably greater than 35% or greater than 40%. As described above, the porosity refers to the proportion of the pores between the negative electrode active material particles in the negative electrode mixture layer 41, and the pores within the active material particles are not included in the porosity. The porosity of the negative electrode mixture layer 41 is controlled so that the volumetric capacity / porosity reaches a target value, and varies according to, for example, the compression conditions of the negative electrode mixture layer 41 during the manufacture of the negative electrode 12. Generally, when the compression force of the negative electrode mixture layer 41 is reduced, the porosity increases, and when the compression force is increased, the porosity decreases. In addition, the porosity of the negative electrode mixture layer 41 can also be controlled by the particle size distribution of the negative electrode active material.
[0049] The upper limit of the porosity of the negative electrode mixture layer 41 is not particularly limited, but even if the porosity is too high, the improvement effect of the cycle characteristics has reached a limit, so it is preferably 65%, and more preferably 60% or 55%. If the porosity of the negative electrode mixture layer 41 is 25% or more and 65% or less or 60% or less, high capacity and high durability can be more highly achieved.
[0050] In the present disclosure, the porosity of the negative electrode mixture layer is measured using a mercury porosimeter.
[0051] (1) After the battery to be evaluated is discharged to 2.5 V, the battery is disassembled and the negative electrode plates are cut out. A plurality of negative electrode plates are placed as samples in a measurement cell of a mercury intrusion porosimeter.
[0052] (2) In order to prevent the gaps between the samples from being counted as pores, the total volume (Vh) of mercury pressed into pores with a pore diameter of 20 μm or more was determined.
[0053] (3) The total volume of mercury (Vh) is divided by the volume of the negative electrode mixture layer in the discharged state (Va) to calculate the porosity (P (%) = Vh × 100 / Va).
[0054] The density of the negative electrode mixture layer 41 is preferably less than 1.2 g / cc. In this case, the improvement effect of the cycle characteristics becomes more significant. From the perspective of both high capacity and high durability, the lower limit of the density is preferably 0.65 g / cc. An example of a preferred range of the density of the negative electrode mixture layer 41 is greater than 0.65 g / cc and less than 1.2 g / cc, or greater than 0.72 g / cc and less than 0.92 g / cc. When the same material is used, the higher the porosity, the lower the density of the negative electrode mixture layer 41.
[0055] In the present disclosure, the density of the negative electrode mixture layer is measured by the following method.
[0056] (1) After the battery to be evaluated is discharged to 2.5 V, the battery is disassembled and the negative electrode plate is cut out and immersed in DMC for cleaning. After vacuum drying at 100° C. for 5 hours, the mass (Wa) of the negative electrode plate is measured.
[0057] (2) After the negative electrode mixture layer was peeled off from the negative electrode plate and ultrasonically cleaned, the mass (Wc) of the negative electrode core was measured.
[0058] (3) The mass of the negative electrode mixture layer is obtained by subtracting the mass of the negative electrode core (Wc) from the mass of the negative electrode plate (Wa). The mass of the negative electrode mixture layer is divided by the volume of the negative electrode mixture layer in the discharged state (Va) to calculate the density of the negative electrode mixture layer (D (g / cc) = (Wa-Wc) / Va).
[0059] The particle expansion rate of the silicon-containing material is preferably 3.0 times or less. From the perspective of improving cycle characteristics, the particle expansion rate of the silicon-containing material is preferably 3.0 times or less, but when the particle expansion rate is too small, there is a tendency for the capacity to decrease. Therefore, the particle expansion rate of the silicon-containing material is preferably 1.1 times or more. An example of a preferred range of the particle expansion rate is 1.1 times or more and 3.0 times or less, more preferably 1.3 times or more and 2.1 times or less. If the particle expansion rate of the silicon-containing material is within this range, it is easy to take into account both high capacity and high durability.
[0060] In this specification, the particle expansion rate of the silicon-containing material is measured by the following method.
[0061] (1) The battery to be evaluated was disassembled and the negative electrode plate was cut out. Metal Li was used as the counter electrode and an ionic liquid was used as the electrolyte to prepare a monopolar battery in which the cross section of the silicon-containing material particles was exposed.
[0062] (2) The monopolar battery was charged at 0.002C at 25°C until the battery voltage reached 0.6V. After pausing for 10 minutes, the battery was discharged at 0.05C until the battery voltage reached 1.9V. The cross section of the silicon-containing material particles was observed in situ using SEM.
[0063] (3) The cross-sectional area of the silicon-containing material particles in the charged state (Spc) and the cross-sectional area of the silicon-containing material particles in the discharged state (Spd) are obtained from the change in the cross-sectional area of the silicon-containing material particles, and the particle expansion rate (Sp = (Spc / Spd)) is calculated. 1.5 ).
[0064] The expansion rate of the negative electrode mixture layer 41 depends on the expansion rate and the addition amount of the negative electrode active material. The expansion rate of the negative electrode mixture layer 41 is preferably 1.5 times or less. In this case, the improvement effect of the cycle characteristics becomes more significant. The lower limit of the expansion rate of the negative electrode mixture layer 41 is not particularly limited, but as an example it is 1.1 times. An example of a preferred range of the expansion rate of the negative electrode mixture layer 41 is greater than 1.1 times and less than 1.5 times, and more preferably greater than 1.2 times and less than 1.4 times. If the expansion rate of the negative electrode mixture layer 41 is within this range, it is easy to take into account both high capacity and high durability.
[0065] In the present disclosure, the expansion rate of the negative electrode mixture layer is measured by the following method.
[0066] (1) The battery to be evaluated was disassembled and the negative electrode plate was cut out. Metal Li was used as the counter electrode and ionic liquid was used as the electrolyte to make a monopolar battery.
[0067] (2) The monopolar battery was charged at 0.1C in a temperature environment of 25°C until the battery voltage reached 5 mV, and after a 20-minute pause, it was discharged at 0.1C until the battery voltage reached 1.0 V.
[0068] (3) The thickness of the negative electrode mixture layer in a charged state (Tac) and the thickness of the negative electrode mixture layer in a discharged state (Tad) are obtained, and the expansion rate of the negative electrode mixture layer is calculated as a ratio of the thicknesses (Sa=Tac / Tad).
[0069] The silicon-containing material is a material containing Si, and as an example, silicon alloys, silicon compounds and composite materials containing Si can be listed. Among them, composite materials containing Si are preferred. The D50 of the silicon-containing material is usually smaller than the D50 of graphite. The volume-based D50 of the silicon-containing material is, for example, greater than 1 μm and less than 20 μm, or greater than 1 μm and less than 15 μm. It should be noted that the silicon-containing material can be used alone or in combination of two or more.
[0070] The preferred silicon-containing material (composite material) is a composite particle comprising an ion-conducting phase and a Si phase dispersed in the ion-conducting phase. The ion-conducting phase is, for example, at least one selected from the group consisting of a silicate phase, a carbon phase, a silicide phase, and a silicon oxide phase. The silicide phase is a phase of a compound composed of Si and an element more positively charged than Si, and as an example, NiSi, Mg2Si, TiSi2, etc. can be cited. The Si phase is formed by dispersing Si in the form of fine particles. The ion-conducting phase is a continuous phase composed of a collection of particles finer than the Si phase.
[0071] The average value of the size (crystallite size) of the Si phase is preferably greater than 1 nm and less than 200 nm, more preferably greater than 1 nm and less than 100 nm. The average value of the size of the Si phase is calculated using the formula D = kλ / Bcosθ (k = 0.89, λ = 0.15418, 2θ = 28.4°, B is the half-maximum full width) and based on the half-value width of the peak (2θ = 28.4°) caused by Si in the XRD pattern. The average size of the Si phase can be, for example, greater than 1 nm and less than 10 nm. By reducing the size of the Si phase, it is possible to suppress the particle expansion rate associated with charge and discharge while maintaining high capacity.
[0072] The composite material may have a conductive layer covering the surface of the ion conductive phase. The conductive layer is composed of a material having a higher conductivity than the ion conductive layer, and forms a good conductive path in the negative electrode mixture layer 41. The conductive layer is, for example, a carbon coating composed of a conductive carbon material. The conductive carbon material can use carbon black such as acetylene black and Ketjen black, graphite, amorphous carbon (amorphous carbon) with low crystallinity, etc. In view of ensuring conductivity and the diffusibility of Li ions to the interior of the particles, the thickness of the conductive layer is preferably more than 1nm and less than 200nm, or more than 5nm and less than 100nm. The thickness of the conductive layer can be measured by observing the cross section of the composite material using an SEM or a transmission electron microscope (TEM).
[0073] The ion-conducting phase may include at least one selected from the group consisting of elements of Group 1 and Group 2 of the periodic table. The ion-conducting layer may be a Li-doped silicon oxide phase. In addition, the ion-conducting phase may include at least one selected from the group consisting of B, Al, Zr, Nb, Ta, V, Y, Ti, P, Bi, Zn, Sn, Pb, Sb, Co, Er, F, W and lanthanide elements.
[0074] An example of a preferred composite material containing Si is a composite material having a sea-island structure in which fine Si is almost uniformly dispersed in an amorphous silicon oxide phase and is composed of the general formula SiO x Composite particles represented by (0<x≤2). The main component of silicon oxide may be silicon dioxide. In addition, the silicon oxide phase may be doped with Li. The content ratio (x) of oxygen to Si is, for example, 0.5≤x<2.0, preferably 0.8≤x≤1.5.
[0075] Another example of a preferred composite material containing Si is a composite particle having a sea-island structure in which fine Si is almost uniformly dispersed in an amorphous silicate phase. A preferred silicate phase is a lithium silicate phase containing Li. The lithium silicate phase is, for example, a phase having the general formula Li 2z SiO (2+z) The phase of the composite oxide represented by (0<z<2). The lithium silicate phase preferably does not contain Li4SiO4(Z=2). Li4SiO4 is an unstable compound and reacts alkaline with water, so it sometimes deteriorates Si and causes a decrease in charge and discharge capacity. From the perspective of stability, productivity, Li ion conductivity, etc., the lithium silicate phase preferably has Li2SiO3(Z=1) or Li2Si2O5(Z=1 / 2) as the main component.
[0076] Another example of a preferred composite material containing Si is a composite particle having a sea-island structure in which fine Si is almost uniformly dispersed in a carbon phase. The carbon phase is preferably an amorphous carbon phase. The carbon phase may contain a crystalline phase component, but preferably has more amorphous phase components. The amorphous carbon phase is composed of a carbon material having an average plane spacing of the (002) plane measured by X-ray diffraction greater than 0.34 nm. It should be noted that the composite material containing the carbon phase may have a conductive layer different from the carbon phase, or may not have the conductive layer.
[0077] [Separator]
[0078] The separator 13 can use a porous sheet with ion permeability and insulation. As specific examples of the porous sheet, microporous films, woven fabrics, non-woven fabrics, etc. can be listed. As the material of the separator 13, polyolefins such as polyethylene and polypropylene, cellulose, etc. are preferred. The separator 13 can be a single-layer structure or a multi-layer structure. In addition, a resin layer with high heat resistance such as aramid resin can be formed on the surface of the separator 13.
[0079] A filler layer containing an inorganic filler may be formed on the interface between the separator 13 and at least one of the positive electrode 11 and the negative electrode 12. Examples of the inorganic filler include oxides containing metal elements such as Ti, Al, Si, and Mg, and phosphate compounds. The filler layer may be formed by applying a slurry containing the filler to the surface of the positive electrode 11, the negative electrode 12, or the separator 13.
[0080] The nonaqueous electrolyte secondary battery 10 having the above-mentioned structure preferably has a charging upper limit voltage of 4.2V and a cutoff voltage of 2.0V. That is, the nonaqueous electrolyte secondary battery 10 preferably has a voltage range of 2.0V or more and 4.2V or less for charging and discharging. More preferably, the charging and discharging is controlled within a voltage range of 2.5V or more and 4.2V or less. In this case, high capacity and high durability can be more highly balanced.
[0081] Example
[0082] Hereinafter, the present disclosure will be further described through examples, but the present disclosure is not limited to these examples.
[0083] <Example 1>
[0084] [Synthesis of positive electrode active material]
[0085] The [Ni 0.90 Al 0.05 Mn 0.05 The composite hydroxide represented by ](OH)2 was calcined at 500°C for 8 hours to obtain an oxide (Ni 0.90 Al 0.05 Mn 0.05 Next, LiOH and the composite oxide were mixed so that the molar ratio of Li to the total amount of Ni, Al and Mn was 1.03:1 to obtain a mixture. The mixture was placed under an oxygen flow with an oxygen concentration of 95% (at a rate of 10 cm 3 The mixture was calcined at a rate of 2 mL / min and a flow rate of 5 L / min per 1 kg of the mixture), and the mixture was calcined from room temperature to 650°C at a heating rate of 2.0°C / min, and then calcined from 650°C to 780°C at a heating rate of 0.5°C / min to obtain a positive electrode active material (lithium-containing transition metal composite oxide).
[0086] [Production of positive electrode]
[0087] The positive electrode active material, acetylene black and polyvinylidene fluoride are mixed in a mass ratio of 98:1:1, and N-methyl-2-pyrrolidone (NMP) is used as a dispersion medium to prepare a positive electrode mixture slurry. Next, the positive electrode mixture slurry is applied to a positive electrode core composed of aluminum foil, the coating is dried and compressed, and then the positive electrode core is cut into a specified electrode size to obtain a positive electrode having a positive electrode mixture layer formed on both sides of the positive electrode core. It should be noted that an exposed portion exposed on the surface of the positive electrode core is provided on a part of the positive electrode.
[0088] [Production of negative electrode]
[0089] As a silicon-containing material, composite particles having a sea-island structure in which fine Si is almost uniformly dispersed in a carbon phase are used (average value of the size of the Si phase: 5 nm, D50: 10 μm, true density: 1.5 g / cc). Using the silicon-containing material as a negative electrode active material, a dispersion of the negative electrode active material, sodium carboxymethyl cellulose (CMC-Na) and styrene-butadiene rubber (SBR) are mixed at a solid component mass ratio of 100:1:1, and water is used as a dispersion medium to prepare a negative electrode mixture slurry. The negative electrode mixture slurry is applied to both sides of a negative electrode core composed of copper foil and the coating is dried, and then the coating is compressed using a roller and cut into a specified electrode size to obtain a negative electrode having a negative electrode mixture layer formed on both sides of the negative electrode core. It should be noted that an exposed portion where the surface of the negative electrode core is exposed is provided on a part of the negative electrode.
[0090] [Preparation of non-aqueous electrolyte]
[0091] Ethylene carbonate (EC), ethyl methyl carbonate (MEC), and dimethyl carbonate (DMC) were mixed in a volume ratio of 3:3:4 (25° C.), and LiPF6 was dissolved in the obtained mixed solvent at a concentration of 1.2 mol / L to prepare a non-aqueous electrolyte.
[0092] [Fabrication of test battery (non-aqueous electrolyte secondary battery)]
[0093] A wound electrode body is obtained by installing leads on the positive electrode and the negative electrode, respectively, and winding the positive electrode and the negative electrode into a spiral shape through a separator. The electrode body is housed in an outer can with a bottom cylindrical shape, and the negative electrode lead is welded to the inner surface of the bottom of the outer can, and the positive electrode lead is welded to the internal terminal plate of the sealing body. Then, the non-aqueous electrolyte is injected into the outer can, and the opening edge of the outer can is tightly fixed to the sealing body to make a cylindrical test battery.
[0094] The particle expansion rate of the silicon-containing material, the density of the negative electrode mixture layer and the expansion rate of the negative electrode mixture layer were measured by the above method. The results showed that the particle expansion rate was 1.78 times, the density of the negative electrode mixture layer was 0.864 g / cc, and the expansion rate of the negative electrode mixture layer was 1.27 times.
[0095] The initial charge and discharge efficiency and cycle characteristics (capacity retention rate) of the above test battery were evaluated by the following method, and the evaluation results are shown in Table 1. The same evaluation was performed on each test battery of the examples and comparative examples described later, and the evaluation results are shown in Table 1 together with the physical properties of the negative electrode. In Table 1, Examples 1 to 10 are designated as A1 to A10, and Comparative Examples 1 to 6 are designated as B1 to B6. The capacity retention rate of each test battery shown in Table 1 is a relative value when the capacity retention rate of the test battery of Example 1 (A1) is designated as 100.
[0096] [Evaluation of initial charge and discharge efficiency]
[0097] For the test battery, at a temperature of 25°C, constant current charging was performed at a current value of 0.5C until the battery voltage reached 4.1V, and then constant voltage charging was performed at 4.1V until the current value reached 0.05C. Then, constant current discharge was performed at a current value of 0.7C until the battery voltage reached 2.85V. The charge capacity and discharge capacity during the charge and discharge period were calculated, and the ratio of the discharge capacity to the charge capacity (discharge capacity × 100 / charge capacity) was calculated as the initial charge and discharge efficiency.
[0098] [Evaluation of Cycle Characteristics (Capacity Retention Rate)]
[0099] The above-described charge and discharge were performed 100 cycles, the discharge capacity at the first cycle and the discharge capacity at the 100th cycle were determined, and the capacity retention rate was calculated by the following formula.
[0100] Capacity retention rate (%) = (100th cycle discharge capacity ÷ 1st cycle discharge capacity) × 100
[0101] <Examples 2 to 10>
[0102] A negative electrode and a nonaqueous electrolyte secondary battery were prepared in the same manner as in Example 1 except that the compression conditions of the negative electrode mixture layer were changed so that the volume specific capacity / porosity of the negative electrode mixture layer was set to the values shown in Table 1, and the above-mentioned performance evaluation was performed.
[0103] <Comparative Examples 1 to 6>
[0104] A negative electrode and a nonaqueous electrolyte secondary battery were prepared in the same manner as in Example 1, except that the compression conditions of the negative electrode mixture layer were changed to set the volume specific capacity / porosity values of the negative electrode mixture layer to the values shown in Table 1. It should be noted that the test batteries of Comparative Examples 4 to 6 were found to have a significant decrease in capacity retention at the beginning of the cycle.
[0105] [Table 1]
[0106]
[0107] As shown in Table 1, the test batteries of the examples all had higher capacity retention rates after the cycle test and better cycle characteristics than the test batteries of Comparative Examples 1 to 6. In addition, the test batteries of the examples had higher initial charge and discharge efficiencies than the test batteries of Comparative Examples 5 and 6.
[0108] From the evaluation results shown in Table 1, it can be seen that when the value of the volumetric capacity / porosity of the negative electrode mixture layer is 48.0 mAh / cc·% or less, it can be understood that the capacity retention rate is significantly improved and the cycle characteristics are improved. In other words, when the value of the volumetric capacity / porosity of the negative electrode mixture layer exceeds 48.0 mAh / cc·%, the cycle characteristics drop sharply. In particular, when the volumetric capacity / porosity exceeds 70 mAh / cc·%, the charge and discharge efficiency also drops significantly.
[0109] As described above, in a non-aqueous electrolyte secondary battery in which the ratio of silicon-containing material in the negative electrode active material is 50 mass % or more, by controlling the volumetric capacity / porosity of the negative electrode mixture layer to be 48.0 mAh / cc·% or less, both high capacity and high durability can be achieved.
[0110] The present disclosure is further illustrated by the following embodiments.
[0111] Solution 1: A negative electrode for a secondary battery, comprising a core and a mixture layer disposed on the core,
[0112] The composite layer contains a silicon-containing material as an active material, the proportion of the silicon-containing material in the active material is greater than 50 mass %, and the porosity of the composite layer is greater than 25%, and the value obtained by dividing the volumetric capacity by the porosity is less than 48.0 mAh / cc·%.
[0113] Aspect 2: The secondary battery negative electrode according to aspect 1, wherein the density of the mixture layer is 1.2 g / cc or less.
[0114] Aspect 3: The negative electrode for a secondary battery according to aspect 1 or 2, wherein a ratio of the silicon-containing material in the active material is 70 mass % or more and 100 mass % or less.
[0115] Aspect 4: The negative electrode for a secondary battery according to any one of aspects 1 to 3, wherein the particle expansion rate of the silicon-containing material is 3.0 times or less.
[0116] Aspect 5: The secondary battery negative electrode according to any one of aspects 1 to 4, wherein the expansion rate of the mixture layer is 1.5 times or less.
[0117] Aspect 6: The secondary battery negative electrode according to any one of aspects 1 to 5, wherein the mixture layer contains at least one carbon material selected from the group consisting of natural graphite, artificial graphite, soft carbon, and hard carbon as the active material.
[0118] Scheme 7: The negative electrode for a secondary battery according to any one of schemes 1 to 6, wherein the silicon-containing material comprises an ion conductive phase and a Si phase dispersed in the ion conductive phase, and the ion conductive phase is at least one selected from the group consisting of a silicate phase, a carbon phase, a silicide phase and a silicon oxide phase.
[0119] Aspect 8: The secondary battery negative electrode according to aspect 7, wherein the volume-based median diameter of the silicon-containing material is 1 μm or more and 20 μm or less, and the average size of the Si phase is 1 nm to 200 nm.
[0120] Aspect 9: A non-aqueous electrolyte secondary battery comprising the secondary battery negative electrode according to any one of aspects 1 to 8, a positive electrode, and a non-aqueous electrolyte, wherein charging and discharging are controlled within a voltage range of 2.0 V to 4.2 V.
[0121] Description of Reference Numerals
[0122] 10 non-aqueous electrolyte secondary battery, 11 positive electrode, 12 negative electrode, 13 separator, 14 electrode body, 16 outer can, 17 sealing body, 18, 19 insulating plate, 20 positive electrode lead, 21 negative electrode lead, 22 groove part, 23 internal terminal plate, 24 lower valve body, 25 insulating member, 26 upper valve body, 27 cover, 28 gasket, 30 positive electrode core body, 31 positive electrode mixture layer, 40 negative electrode core body, 41 negative electrode mixture layer
Claims
1. A negative electrode for a secondary battery, comprising a core and a mixture layer disposed on the core, The composite layer contains a silicon-containing material as an active material, the proportion of the silicon-containing material in the active material is greater than 50 mass %, and the porosity of the composite layer is greater than 25%, and the value obtained by dividing the volumetric capacity by the porosity is less than 48.0 mAh / cc·%.
2. The negative electrode for a secondary battery according to claim 1, wherein The silicon-containing material accounts for 70% by mass or more of the active material.
3. The negative electrode for a secondary battery according to claim 1, wherein The density of the mixture layer is 1.2 g / cc or less.
4. The negative electrode for a secondary battery according to claim 1, wherein The particle expansion rate of the silicon-containing material is less than 3.0 times.
5. The negative electrode for a secondary battery according to claim 1, wherein The expansion rate of the mixture layer is 1.5 times or less.
6. The negative electrode for a secondary battery according to claim 1, wherein The mixture layer contains at least one carbon material selected from the group consisting of natural graphite, artificial graphite, soft carbon, and hard carbon as the active material.
7. The negative electrode for a secondary battery according to claim 1, wherein The silicon-containing material comprises an ion-conducting phase and a Si phase dispersed in the ion-conducting phase, The ion-conducting phase is at least one selected from the group consisting of a silicate phase, a carbon phase, a silicide phase, and a silicon oxide phase.
8. The negative electrode for a secondary battery according to claim 7, wherein The volume-based median particle size of the silicon-containing material is greater than or equal to 1 μm and less than or equal to 20 μm, The average value of the size of the Si phase is greater than or equal to 1 nm and less than or equal to 200 nm.
9. A non-aqueous electrolyte secondary battery comprising the secondary battery negative electrode according to any one of claims 1 to 8, a positive electrode, and a non-aqueous electrolyte, Charging and discharging are controlled within a voltage range of 2.0V or more and 4.2V or less.
Citation Information
Patent Citations
Novel material having highly durable lithium insertion and method for manufacturing the same
JP2018534720A